Network architecture and sex chromosome turnovers: Do epistatic interactions shape patterns of sex chromosome replacement?. (7th December 2020) - Tao, Wenjing; Conte, Matthew A.; Wang, Deshou; Kocher, Thomas D.
Abstract: Recent studies have revealed an astonishing diversity of sex chromosomes in many vertebrate lineages, prompting questions about the mechanisms of sex chromosome turnover. While there is considerable population genetic theory about the evolutionary forces promoting sex chromosome replacement, this theory has not yet been integrated with our understanding of the molecular and developmental genetics of sex determination. Here, we review recent data to examine four questions about how the structure of gene networks influences the evolution of sex determination. We argue that patterns of epistasis, arising from the structure of genetic networks, may play an important role in regulating the rates and patterns of sex chromosome replacement. Abstract : The structure of gene networks determines the epistatic relationships of mutations in the sex‐determining pathway. Selection favors the invasion of new mutations that are epistatically dominant to the existing sex determining gene. Therefore, network architecture may regulate the rates and patterns of sex chromosome turnover.